POLYVINYLIDENE FLUORIDE MEMBRANES WITH TIN (IV) DIOXIDE (SNO2) ADDITIVES: ENHANCING WATER TREATMENT FOR AIRPORT ECO GREEN - Muhammad Rafli Fazal; Agung Mataram (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2023)
Water treatment is a significant process of realizing Eco Airport in airport development that does not cause environmental damage, protects the environment, and seeks to minimize the impact of environmental pollution due to airport operations. The growth and development of the global economy make a significant contribution resulting in increasingly uncontrolled disposal of wastewater, resulting in a series of environmental problems related to providing clean water at airports. This study discusses water filtration using membrane technology with Polyvinylidene Fluoride (PVDF) polymer mixed with Tin (IV) Dioxide (SnO2). This study aims to analyze the microstructure formed through Scanning Electron Microscopy (SEM) testing and determine the mechanical properties and performance in water treatment of mixed PVDF and Tin (IV) Dioxide (SnO2) membranes. This research is a new method in water treatment. The research method used was quantitative with initial membrane specimen formation, membrane preparation, flat sheet method, and testing methods (tensile testing, Scanning Electron Microscopy (SEM) observations, and Clean Water Permeability (CWP) testing. The results of this study, namely the formation of mixed membranes, showed the corresponding results as an alternative to water filter membranes. PVDF and SnO2 mixed membranes subjected to tensile tests using ASTM D638 standards, the surface structure of mixed membranes using SEM showed significant differences at each concentration, and the performance of water treatment performed with CWP showed an increase with increasing PVDF concentration and SnO2 for the airport. The conclusion is that water treatment performance using Clean Water Permeability (CWP) increases with increasing concentrations of PVDF and SnO2, which are suitable for airports.